Answer:
y = [tex]8(-\frac{1}{2})^x[/tex]
Step-by-step explanation:
Let the equation of the exponential function is,
y = a(b)ˣ
Since the graph of this function passes through two points [tex](4, \frac{1}{2})[/tex] and (3, -1)
For the point [tex](4, \frac{1}{2})[/tex],
[tex]\frac{1}{2}=a(b)^4[/tex] ---------(1)
For second point (3, -1),
-1 = a(b)³ ---------(2)
Divide equation (2) by equation (1),
[tex]\frac{\frac{1}{2}}{-1}[/tex] = [tex]\frac{a(b)^4}{a(b)^3}[/tex]
[tex]-\frac{1}{2}=b^{(4-3)}[/tex]
[tex]-\frac{1}{2}=b[/tex]
From equation (2)
-1 = [tex]a(-\frac{1}{2})^3[/tex]
-1 = [tex]-\frac{1}{8}a[/tex]
a = 8
Therefore, equation of the exponential function will be,
y = [tex]8(-\frac{1}{2})^x[/tex]